The effectiveness of postoperative delirium prevention, diagnosis, and intervention protocol in patients monitored in the intensive care unit after cardiac surgery: a quasi-experimental study - Gönül Kara Söylemez; Hülya Bulut (BMC Nursing)
Abstract Background The incidence of delirium is high in the intensive care unit (ICU) after cardiac surgery. The development of evidence-based care protocols for delirium management and training of nurses in this regard can ensure effective management of delirium. This quasi-experimental study aimed to assess the effectiveness of a postoperative delirium prevention, diagnosis, and intervention protocol in patients undergoing monitoring in the ICU after cardiac surgery. Methods This study included 64 patients who underwent cardiac surgery and met the inclusion criteria, along with 14 nurses working in the ICU. Patients were divided into control (n = 32) and intervention (n = 32) groups. The study comprised three phases: determining the incidence of delirium in the control group and the delirium diagnosis status of the nurses; providing training to nurses on postoperative delirium prevention, diagnosis and intervention protocol; implementing a preliminary study of the protocol; and finally, implementing the protocol in the intervention group. Statistical significance was set at p < 0.05. Results While there was no significant agreement in delirium diagnosis between researcher and nurses in the control group (kappa: 0.207) (p > 0.05), significant agreement was observed in the intervention group (kappa: 1.00) (p < 0.001). The delirium diagnosis rate of the nurses was 14.3% in the control group and 100% in the intervention group, which was a significant difference. The incidence of delirium was 21.9% in the control group and 9.4% in the intervention group, although the difference was not significant. Conclusion Postoperative delirium prevention, diagnosis, and intervention protocol effectively enhance delirium diagnosis compliance among researchers and nurses and improve the accuracy of delirium diagnosis among postcardiac surgery ICU patients. The implementation of this protocol is recommended for delirium management in such patients. Trial registration This study was retrospectively registered at Clinicaltrials.gov on 19.02.2024 (Clinical Trials ID: NCT06268119).